2021
DOI: 10.3389/fmed.2020.609158
|View full text |Cite
|
Sign up to set email alerts
|

The Blockade of TACE-Dependent EGF Receptor Activation by Losartan-Erlotinib Combination Attenuates Renal Fibrosis Formation in 5/6-Nephrectomized Rats Under Vitamin D Deficiency

Abstract: Chronic kidney disease (CKD) has been considered a major public health issue. In addition to cardiovascular diseases and infections, hypovitaminosis D has been considered a non-traditional aggravating factor for CKD progression. Interstitial fibrosis is a hallmark of CKD strongly correlated with deterioration of renal function. Transforming growth factor β (TGF-β) is the major regulatory profibrotic cytokine in CKD. Many injurious stimuli converge on the TGF-β pathway, which has context-dependent pleiotropic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 66 publications
(148 reference statements)
1
6
0
2
Order By: Relevance
“…Corroborating our results, Decleves et al also observed increased renal and urinary expression of MCP-1 in mice fed a high-fat diet ( 35 ). In the present study, we also observed similar results concerning the renal expression of MCP-1, CD3+, and CD68+ cells in the VDD group, reinforcing the immunomodulatory effect of vitamin D ( 1 , 7 , 77 ). Of note, we found a higher renal expression of MCP-1, CD3+, and CD68+ cells in the HFDV group compared to all the other groups, demonstrating a synergistic effect of adipose tissue and vitamin D deficiency regarding the inflammatory process.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Corroborating our results, Decleves et al also observed increased renal and urinary expression of MCP-1 in mice fed a high-fat diet ( 35 ). In the present study, we also observed similar results concerning the renal expression of MCP-1, CD3+, and CD68+ cells in the VDD group, reinforcing the immunomodulatory effect of vitamin D ( 1 , 7 , 77 ). Of note, we found a higher renal expression of MCP-1, CD3+, and CD68+ cells in the HFDV group compared to all the other groups, demonstrating a synergistic effect of adipose tissue and vitamin D deficiency regarding the inflammatory process.…”
Section: Discussionsupporting
confidence: 88%
“…Inflammatory cells including macrophages and T cells play a key role in tissue homeostasis and immune responses, especially in the course of kidney diseases ( 7 , 77 ). Moreover, an exacerbated inflammatory response is usually associated with a growing RFF ( 7 , 77 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations